The Impact of Financial Management on Business Growth in MSMEs: A Literature Review - Permana, Hendrik; Saepuloh, Aep; Judijanto, Loso; Mahmudah, Mahmudah; Hendra, Muhammad (The Future of Education Journal, 2025)
This study aims to analyze the impact of financial management on the business growth of SMEs based on existing literature. Effective financial management plays a crucial role in supporting the sustainability and development of SMEs. Efficient cash flow management, cost control, and proper risk management are key factors influencing the stability and profitability of SMEs. Furthermore, wise investment decisions can drive business expansion and increase market competitiveness. However, challenges faced by SMEs, such as limited access to financing and a lack of understanding in financial management, need more attention. This study suggests the importance of financial management education and training for SME owners to enhance their financial management skills and support sustainable business growth. The method used in this research is library research with a descriptive analysis approach to relevant literature from various sources, including books, journals, and scholarly articles.